CRYOTHERAPY MODALITIES IN PHYSICALLY ACTIVE INDIVIDUALS: EFFECTS ON RECOVERY, PERFORMANCE, AND PHYSIOLOGICAL HEALTH - A NARRATIVE REVIEW - Hubert Woźniak,; Anna Maria Gęsińska,; Krystian Czyżykowski,; Helena Szelka,; Paweł Edyko,; Alicja Babula,; Wiktor Golus,; Katarzyna Andrzejewska,; Zuzanna Przybyła,; Bartosz Golis, (International Journal of Innovative Technologies in Social Science, 2025)
The aim of this narrative review was to analyze the impact of commonly used forms of cryotherapy - primarily cold-water immersion (CWI) and whole-body cryotherapy (WBC) - on post-exercise recovery, exercise capacity, and selected indicators of physiological health in physically active individuals. The review included publications, including meta-analyses, randomized trials, and experiments involving athletes and recreational exercisers, assessing short- and long-term effects. The available evidence indicates that CWI generally reduces post-workout muscle soreness and improves the subjective feeling of recovery, and in many studies also reduces the increase in markers of muscle damage, although this effect is not uniform and depends on the parameters of the intervention. WBC, on the other hand, has a stronger systemic anti-inflammatory and antioxidant effect, especially in multi-session protocols. Both the effectiveness and possible limitations of both modalities depend on the dose, temperature, immersion time, timing of application, and nature of the training load. All available data indicate that cryotherapy, when used properly and in accordance with safety standards, is a valuable tool for supporting sports recovery, while its impact on performance is mainly indirect, through reducing fatigue and accelerating the recovery of muscle function.